The Behaviour of Consumer and Strategy of Development of Legal Metrology Performance - Rifan Ardianto; Bonita Oktriana (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
This study explores the knowledge, attitude, and practice (KAP) in legal metrology since there is very little information on knowledge, attitude, and practice concerning legal metrology. The survey data gathered from 24.360 respondents across 34 provinces in Indonesia assessed the understanding concerning legal metrology by applying descriptive statistics, correlation, and multinomial regression analysis. The results show the consumers generally have better knowledge in legal metrology, an excellent attitude about the importance of legal metrology, and critical behaviour in mitigating fraudulence risk when doing trade transactions at the marketplace. Variable of gender and age tends to impact knowledge, attitude, and practice concerning legal metrology issues. The study also found that the relationship between knowledge, attitude, and practice is likely to be non-linear. The outcomes of exploring the behaviour of consumers through knowledge, attitude, and practice in legal metrology can be beneficial for legal metrology authorities to analyze the impact of setting policies and programs. Also, to develop a strategy to increase public awareness in legal metrology so that the consumers can be more critical in protecting themselves from various fraudulence in measurement in trade transactions.